Thick vs. thin tongue coatings in hemodialysis patients: unveiling gut microbiome dysregulation and systemic health implications - Wang, Yuqing; Zeng, Xueyan; Wu, Mengqi; Lu, Bin; Wang, Jiarui; Chen, Saiping; Zhang, Aiping; Huang, Min; Zhu, Yanqin; Liu, Hong; Zhu, Fenggui; Chen, Shilei; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundGastrointestinal (GI) disturbances are prevalent in maintenance hemodialysis (MHD) patients and are closely associated with gut microbiota dysregulation. Tongue coating thickness, a key diagnostic feature in traditional Chinese medicine, may reflect systemic and microbial health. This study aimed to explore the relationship between tongue coating phenotype and gut microbiota composition in MHD patients.MethodsA matched case-control study was conducted involving 30 MHD patients divided into thick (HTZ, n = 15) and thin (BTZ, n = 15) tongue coating groups, along with 15 healthy controls (DZZ). Fecal samples were analyzed via 16S rRNA sequencing to assess microbial diversity, taxonomic profiles, and predicted functional pathways.ResultsAlpha-diversity indices were significantly lower in BTZ than in DZZ (q < 0.05), while no difference was found between HTZ and BTZ. Beta-diversity showed closer clustering between HTZ and BTZ than with DZZ. Compared to DZZ, both HTZ and BTZ exhibited reduced levels of genera typically associated with health or commensal functions (Romboutsia, Subdoligranulum) and increased abundances of taxa often linked to inflammation or disease (Escherichia-Shigella, Ruminococcus gnavus). Functional predictions indicated that HTZ was enriched in pathways related to disease processes and showed diminished cellular and metabolic functions.ConclusionTongue coating thickness in MHD patients reflects underlying gut microbial composition. Thick tongue coatings indicate a state of dysbiosis with potential health implications, whereas thin coatings are associated with a microbiota profile that may be more favorable. These findings support the potential use of tongue coating thickness as a noninvasive biomarker for gut health assessment in clinical nephrology.